Tahap motivasi holistik, intrinsik dan ekstrinsik terhadap pembelajaran kosa kata bahasa arab dalam kalangan graduan universiti awam - Asbulah L.H.; Lubis M.A.; Aladdin A.; Sahrim M. (Penerbit Universiti Sains Malaysia, 2024)
The purpose of this study is to evaluate the students’ motivation levels towards learning Arabic language vocabulary among Arabic language graduate students in public universities. The motivational domains that had been analysed in this study were holistic, intrinsic and extrinsic. A total of 344 Arabic language graduate students had been used as respondents in this study. This study is a cross-sectional study involving final year Arabic language students from eight public universities. Futhermore, simple random sampling was used as a sampling method based on the ability of the researcher to obtain the sampling frame. The data was analysed using IBM SPSS version 19.0 descriptively such as mean, standard deviation and percentage. The findings showed that the motivation Arabic language graduate students to learn the Arabic vocabulary for holistic motivation was at a high level followed by extrinsic and intrinsic domains at a moderate level. Therefore, this study revealed the differences in findings that religious or holistic factor was a main factor of Muslim students to continue studying Arabic language vocabulary. However, research in western findings showed that rewards, recognition and external returns were the factors to learn the vocabulary of language.